Field Evaluation of a PCR Test for Schistosoma japonicum Egg Detection in Low-Prevalence Regions of China - Fung, Mai S. (The American Society of Tropical Medicine and Hygiene, 2012)
Sensitive Schistosoma japonicum detection methods are needed to progress from schistosomiasis control to elimination. The sensitivity of the Kato-Katz thick smear and miracidium hatching tests decrease with infection intensity and serological tests cannot always identify current infections. We evaluated a fecal polymerase chain reaction (PCR) assay to detect S. japonicum infection in 106 humans and 8 bovines in China. PCR was highly sensitive, detecting S. japonicum DNA at 0.5 eggs/g of stool. Comparing PCR examination of a single stool sample to the miracidium hatching test using three consecutive stool samples, more humans were hatching test positive (20%) than PCR positive (15%). However, two individuals were PCR positive in a village where no infections were detected by coprological methods. The sensitivity of PCR makes it a promising tool for schistosomiasis diagnostics and screening, although egg shedding variability and stool sample size present challenges for any detection method in low-transmission areas.